The gut microbial metabolite, 3,4-dihydroxyphenylpropionic acid, alleviates hepatic ischemia/reperfusion injury via mitigation of macrophage pro-inflammatory activity in mice - Rui Li; Li Xie; Lei Li; Xiaojiao Chen; Tong Yao; Yuanxin Tian; Qingping Li; Kai Wang; Chenyang Huang; Cui Li; Yifan Li; Hongwei Zhou; et al. (Elsevier, 2022)
Hepatic ischemia/reperfusion injury (HIRI) is a serious complication that occurs following shock and/or liver surgery. Gut microbiota and their metabolites are key upstream modulators of development of liver injury. Herein, we investigated the potential contribution of gut microbes to HIRI. Ischemia/reperfusion surgery was performed to establish a murine model of HIRI. 16S rRNA gene sequencing and metabolomics were used for microbial analysis. Transcriptomics and proteomics analysis were employed to study the host cell responses. Our results establish HIRI was significantly increased when surgery occurred in the evening (ZT12, 20:00) when compared with the morning (ZT0, 08:00); however, antibiotic pretreatment reduced this diurnal variation. The abundance of a microbial metabolite 3,4-dihydroxyphenylpropionic acid was significantly higher in ZT0 when compared with ZT12 in the gut and this compound significantly protected mice against HIRI. Furthermore, 3,4-dihydroxyphenylpropionic acid suppressed the macrophage pro-inflammatory response in vivo and in vitro. This metabolite inhibits histone deacetylase activity by reducing its phosphorylation. Histone deacetylase inhibition suppressed macrophage pro-inflammatory activation and diminished the diurnal variation of HIRI. Our findings revealed a novel protective microbial metabolite against HIRI in mice. The potential underlying mechanism was at least in part, via 3,4-dihydroxyphenylpropionic acid-dependent immune regulation and histone deacetylase (HDAC) inhibition in macrophages.